Peran Media dalam Membangun Citra dan Narasi Model Bisnis Sosial di Kopi Tuli (Koptul) - Putra Rizki Julainto; Luhur Prasetiyo (Edupreneurship: Jurnal Pendidikan Ekonomi, 2026)
Social business models have developed as an economic approach that balances profit goals and social missions. One prominent example in Indonesia is Kopi Tuli (Koptul), a social enterprise that empowers Deaf individuals by creating an inclusive workspace and providing services based on sign language. This study aims to analyze how the media construct the image and narrative of Koptul as a social enterprise through framing processes, narrative construction, and digital representation. A qualitative approach is applied using content analysis of online news coverage, social media posts, and other public documentation related to Koptul’s activities and social values. Thematic analysis was conducted to identify patterns of framing and media representation. The findings reveal that the media consistently frame Koptul as a social movement born from the founders’ experiences of discrimination. Through framing mechanisms, the media highlight narratives of empowerment, inclusivity, and the struggle for equal employment rights for the Deaf community. Koptul’s positive image is built through narratives emphasizing humanitarian values, solidarity, and the professional competence of Deaf baristas. The media also construct Koptul’s social business model as a social innovation that integrates economic value with social impact through the unique experience of enjoying coffee while learning sign language. Meanwhile, social media plays a significant role in strengthening Koptul’s digital identity through visual content that amplifies messages of inclusivity. In conclusion, the media have a substantial influence on shaping the image and narrative of Koptul as a credible, inclusive, and sustainable social business model. These findings underscore that media support is essential in enhancing legitimacy, visibility, and public acceptance of disability-based social enterprises.